Pengembangan Modul Pembelajaran Berbasis Augmented Reality Mata Pelajaran Fikih Materi Penyembelihan di MTsN 5 Bojonegoro - Putri Eka Nurus Syamsiyah; Hamam Burhanuddin; Ida Fauziatun Nisa3 (Advances In Education Journal, 2025)
The advancement of digital technology demands innovative educational strategies to enhance learning quality and engagement. This study aims to develop an interactive learning module integrating Augmented Reality (AR) technology through the Assemblr Edu application, specifically for the Islamic jurisprudence (Fiqh) subject, focusing on the topic of animal slaughtering. This development allows students to visualize the slaughtering process in 3D using Google Lens, thereby improving their conceptual understanding. The research applied a Research and Development (R&D) approach using the ADDIE model and was conducted over two months at MTsN 5 Bojonegoro. Participants included a content expert, a media expert, a Fiqh teacher, and students from class IX-D. Data were collected through expert validation sheets and student questionnaires, and analyzed using both qualitative and quantitative methods. The content expert validation yielded a score of 97,92%, the media expert validation reached 97.92%, and the practicality assessment achieved 95.83%, all falling under the category of "highly feasible." These results indicate that the AR-based learning module is pedagogically appropriate, media-efficient, and practical for classroom implementation.